2011
DOI: 10.1002/jbm.b.31787
|View full text |Cite
|
Sign up to set email alerts
|

Development of a biodegradable tissue adhesive based on functionalized 1,2‐ethylene glycol bis(dilactic acid). II.

Abstract: In body regions where damage and bleeding must be avoided, a substitute for mechanical tissue fixation by sutures or staplers is needed. Since tissue adhesives provide easy and fast handling they are a promising alternative. The present study reports the development and analysis of a tissue adhesive that consists of two adhesive components: hexamethylene diisocyanate (HDI) functionalized 1,2-ethylene glycol bis(dilactic acid) (ELA-NCO) and chitosan chloride. This composition was chosen based on preliminary stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 27 publications
1
13
0
Order By: Relevance
“…When used as an LDD system for long-term release, the swelling properties of the hydrogel have to be greatly reduced, which can be achieved by crosslinking HA with ELA-NCO. ELA-NCO is a hydrophobic isocyanate functionalized 1,2-ethylene glycol bis(dilactic), which has been previously investigated as part of a drug eluting tissue adhesive formula [19,22,40]. Micro-CT measurements showed that HA/ELA-NCO has a highly porous structure, which is advantageous for drug release and leads to softness.…”
Section: Figure 10mentioning
confidence: 99%
See 2 more Smart Citations
“…When used as an LDD system for long-term release, the swelling properties of the hydrogel have to be greatly reduced, which can be achieved by crosslinking HA with ELA-NCO. ELA-NCO is a hydrophobic isocyanate functionalized 1,2-ethylene glycol bis(dilactic), which has been previously investigated as part of a drug eluting tissue adhesive formula [19,22,40]. Micro-CT measurements showed that HA/ELA-NCO has a highly porous structure, which is advantageous for drug release and leads to softness.…”
Section: Figure 10mentioning
confidence: 99%
“…Previously, the biocompatibility of LDD components has been separately demonstrated for both, HA and ELA-NCO [19,41]. Among glaucoma drugs, LA was chosen for drug release experiments, because, as already mentioned, the current literature lacks any data concerning long-term subconjunctival LA delivery.…”
Section: Figure 10mentioning
confidence: 99%
See 1 more Smart Citation
“…In one of the employed strategies a two-component adhesive formulation consisting of a hyper-branched adhesive component and a cross-linking mixture with an amine group-containing compound was used. It is known that amine groups have up to 50 times higher reactivity towards isocyanate-groups than hydroxyl groups, and using such composition will allow the glue to cure within significantly shorter times [8, 9, 15]. The adhesive was applied using a double-chamber syringe equipped with a static mixer.…”
Section: Discussionmentioning
confidence: 99%
“…Few strategies have been employed to speed up the curing rates of isocyanate-terminated polymers. Sternberg et al engaged the use of polymers such as hyaluronic acid, gelatin, chitosan acetate, and chitosan chloride, which were mixed with the isocyanate-terminated adhesive component prior to its application [8, 9]. Another strategy was chosen by Beckman et al .…”
Section: Introductionmentioning
confidence: 99%